Using the automationml ar apc recommendation for integration of engineering tools in the control system lifecycle - Pupena, O. (Energy and Automation, 2026)
Automation of software creation is possible when frameworks are available, one of which is PACFramework. However, automation tools require consistency with computer-aided engineering systems, which implies automated data import and export. Therefore, neutral data representation models are increasingly used to ensure interoperability between engineering tools. One of the standards designed for engineering data exchange in industrial automation is AutomationML. In particular, the AutomationML Application Recommendation Automation Project Configuration (AR APC) defines a model for representing the hardware configuration of automation systems. This paper investigates the applicability of the AR APC recommendation as a format for representing hardware configuration and master data in the lifecycle of industrial control systems. The study is carried out in the context of the PFw2 lifecycle architecture, where master data are considered a central element for the integration of engineering tools. The structure of the AR APC model is analyzed with respect to its capability to represent devices, modules, channels, and process variables. Based on this analysis, the correspondence between AR APC elements and the lower levels of the PFw2 control model is examined. The results show that the AR APC model fully covers the Channels sublevel and partially covers the Process Variables sublevel in the hierarchy of the control model. Therefore, the model can be used as a basis for representing lower-level master data and for integrating engineering tools used in the lifecycle of industrial control systems. The results demonstrate the potential of using AutomationML AR APC to ensure consistent engineering data exchange between different engineering environments. Recieved: 27.12.2025. Recieved: 19.02.2026. Accepted: 17.04.2026.